2022
DOI: 10.1111/srt.13199
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a novel microneedle patch for rejuvenation of the nasolabial fold

Abstract: Background: Skin rejuvenation plays a significant role in the esthetic medicine market. Microneedle patches have been developed for a wide range of applications based on the principles of transdermal drug delivery; however, clinical trials of microneedle patches for skin rejuvenation remain limited.Aims: This study was conducted to examine the efficacy of microneedle patches for improving nasolabial folds.Methods: A total of 23 Thai women completed this prospective clinical trial. The participants were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“… 6 Nasolabial folds look like wrinkles, because both are shaped by folding of the dermis. Several aesthetic techniques are used for nasolabial rejuvenation like microneedle, 7 , 8 radiofrequency, 9 and filler injection 10 , 11 , 12 , 13 but each method has its own risks. Ablative laser resurfacing by erbium: YAG (Er:YAG) laser and carbon dioxide laser is an effective method for rejuvenation of the skin but has probable side effects like, infection, prolonged erythema, and scarring.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Nasolabial folds look like wrinkles, because both are shaped by folding of the dermis. Several aesthetic techniques are used for nasolabial rejuvenation like microneedle, 7 , 8 radiofrequency, 9 and filler injection 10 , 11 , 12 , 13 but each method has its own risks. Ablative laser resurfacing by erbium: YAG (Er:YAG) laser and carbon dioxide laser is an effective method for rejuvenation of the skin but has probable side effects like, infection, prolonged erythema, and scarring.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study in Thailand, 23 female Thai participants were treated with MNP and 1.8% hyaluronic acid (HA) to the right and left nasolabial folds. Patients treated with the MNP alone experienced significant improvements in their scores [18], with no differences reported in the improvement in wrinkles between the two groups. Similarly, treatment with 0.23 mm non-absorbable magnesium MNP under the eyes showed improvement in the grade of skin wrinkles and the index of dermal thickness after 12 weeks [15].…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, the same type of MNP has also been developed for combined use with drug delivery and LED light therapy. In previous studies, it was found to be effective and free of adverse effects [18,24].…”
Section: Discussionmentioning
confidence: 98%
“…Henry et al were the first to apply microneedles in the mainstream drug delivery field, sparking a boom in the industrialization of microneedles [ 139 ]. The length, height, and shape of microneedles can be individually tailored according to therapeutic requirements [ 140 , 141 ], and they can be categorized based on their morphology as solid, hollow, coated, dissolvable, and hydrogel microneedles. Microneedles based on BP, which exhibit photothermal conversion properties, have garnered significant attention in the field of skin tissue repair [ 142 ].…”
Section: Bp-based Composite Biomaterials For Tissue Repairmentioning
confidence: 99%